The economic history of Latin America since independence - Bulmer-Thomas, V. (Cambridge : Cambridge University Press, 2014)
This study, now in a revised and updated third edition, covers the economic history of Latin America from independence in the 1820s to the present. It stresses the differences between Latin American countries while recognizing the external influences to which the whole region has been subject. Victor Bulmer-Thomas notes the failure of the region to close the gap in living standards between it and the United States and explores the reasons. He also examines the new paradigm taking shape in Latin America since the debt crisis of the 1980s and asks whether this new economic model will be able to bring the growth and improvement in equity that the region desperately needs. This third edition contains a wealth of new material that draws on the new research in the area in the past ten years.
Latin American economic development: an overview -- The struggle for national identity from independence to midcentury: The colonial legacy ; The economic consequences of independence ; The free-trade question ; The export sector ; The nonexport economy ; Regional differences -- The export sector and the world economy, circa 1850-1914: World demand and the export-led growth model ; Export performance ; Export cycles ; The pattern of external trade ; The terms of trade and international transport costs -- Export-led growth : the supply side: The labor market ; Land ; Capital markets ; Foreign investment ; The policy context -- Export-led growth and the nonexport economy : Domestic-use agriculture ; Manufacturing and its origins ; Industry and relative prices ; Regional differences on the eve of the First World War -- The First World War and its aftermath: The collapse of the old order ; Trade strategies ; Exchange-rate, financial, and fiscal reform ; External shocks, relative prices, and the manufacturing sector -- Policy, performance, and structural change in the 1930s: The Depression of 1929 ; Short-term stabilization ; Recovery from the Depression ; The international environment and the export sector ; Recovery of the non-export economy ; The transition toward inward-looking development -- War and the new international economic order: Trade and industry in the Second World War ; Trade surpluses, fiscal policy, and inflation ; The postwar dilemma ; The new international economic order -- Inward-looking development in the postwar period: The inward-looking model ; Outward-looking countries ; Regional integration ; Growth, income distribution, and poverty -- New trade strategies and debt-led growth ; Export promotion ; Export substitution ; Primary export development ; The state, public enterprise, and capital accumulation ; Debt-led growth -- Debt, adjustment, and the shift to a new paradigm ; From debt crisis to debt burden ; External adjustment ; Internal adjustment, inflation stabilization, and the exchange-rate problem ; Growth, poverty, and income distribution, since the debt crisis -- Conclusions.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Latin America -- Economic conditions; Latin America -- Economic policy